Pre-existing hyperlipidaemia increased the risk of new-onset anxiety disorders after traumatic brain injury: a 14-year population-based study. Issue 7 (17th July 2014) - Ho, Chung-Han; Hsieh, Kuang-Yang; Liang, Fu-Wen; Li, Chia-Jung; Wang, Jhi-Joung; Chio, Chung-Ching; Chang, Chin-Hung; Kuo, Jinn-Rung
Abstract : Objectives: Anxiety disorders (ADs) are common after traumatic brain injury (TBI). However, the risk factors of new-onset ADs remain unclear. This study was aimed at evaluating the incidence and risk factors for new-onset ADs, including pre-existing hyperlipidaemia and three major comorbidities (diabetes mellitus, hypertension and cardiovascular disease), in patients with TBI. Setting: A matched cohort study was conducted using the Taiwan Longitudinal Health Insurance Database between January 1997 and December 2010. Participants: A total of 3822 participants (1274 patients with TBI with hyperlipidaemia and 2548 age-matched and gender-matched patients with TBI without hyperlipidaemia). Outcome measures: The incidence and HRs for the development of new-onset ADs after TBI were compared between the two groups. Results: The overall incidence rate of new-onset ADs for patients with TBI with hyperlipidaemia is 142.03/10 000 person-years (PYs). Patients with TBI with hyperlipidaemia have a 1.60-fold incidence rate ratio (p<0.0001) and increased HR of ADs (1.58, 95% CI 1.24 to 2.02) compared with those without hyperlipidaemia. The incidence rates of ADs for males and females with hyperlipidaemia, respectively, were 142.12 and 292.32/10 000 PYs, which were higher than those without hyperlipidaemia (93.03 and 171.68/10 000 PYs, respectively). Stratified by age group, hyperlipidaemia is a risk factor of ADs for patients with TBI aged 65 years or younger. Conclusions: Pre-existing hyperlipidaemia is an independent predictor of new-onset ADs in patients with TBI, even when controlling for other demographic and clinical variables. Female patients with pre-existing hyperlipidaemia had significantly higher risk of new-onset ADs than males, especially between the ages of 35 and 65 years.